2016
DOI: 10.1111/2041-210x.12700
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic processing of RAD‐seq data dramatically impacts downstream population genetic inference

Abstract: Summary Restriction site‐associated DNA sequencing (RAD‐seq) provides high‐resolution population genomic data at low cost, and has become an important component in ecological and evolutionary studies. As with all high‐throughput technologies, analytic strategies require critical validation to ensure precise and unbiased interpretation. To test the impact of bioinformatic data processing on downstream population genetic inferences, we analysed mammalian RAD‐seq data (>100 individuals) with 312 combinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
312
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 282 publications
(332 citation statements)
references
References 70 publications
15
312
5
Order By: Relevance
“…Recent studies using restriction-site associated DNA sequencing (RAD-seq) have shown that overall data quality is considerably higher when using a reference (Fountain et al. 2016; Shafer et al. 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using restriction-site associated DNA sequencing (RAD-seq) have shown that overall data quality is considerably higher when using a reference (Fountain et al. 2016; Shafer et al. 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, allele frequency estimates remained similar between individual-based methods and Pool-seq, except for one pool. Moreover, as stipulated by Shafer et al (2017), it is difficult to reproduce the important variation introduced during wet laboratory data generation using simulated data. (a, b, and c) represent the eigenvalue decomposition of the scaled variance-covariance matrices of population allele frequencies (Ω) for GBS, Rapture, and Pool-seq datasets, respectively.…”
Section: Level Of Congruence Between Gbs and Alternatives Methodsmentioning
confidence: 99%
“…Furthermore, filtering choices (see figure 2 in Benestan et al., 2016) can greatly influence downstream summary statistics. A recent study testing the impact of data processing on population genetic inferences using RAD‐seq data observed large differences between reference‐based and de novo approaches in population genetic summary statistics, particularly those based on the site frequency spectrum (Shafer et al., 2016). In addition, the recent debate over the effectiveness of RAD‐seq for discovering loci under selection (Catchen et al., 2017; Lowry et al., 2016; McKinney, Larson, Seeb, & Seeb, 2017) has highlighted the importance of testing the extent of linkage disequilibrium (LD) over the genome, whenever possible, in order to assess the power of genome scans to detect selected loci (e.g., Kardos, Taylor, Ellegren, Luikart, & Allendorf, 2016).…”
Section: Genotyping Error and Improving Data Qualitymentioning
confidence: 99%
“…On the other hand, imposing MAF filters that are too strict (e.g., above 0.05 or 0.1) could skew metrics based on the site frequency spectrum or inadvertently remove loci under selection or with functional significance. As others have recommended, testing the effects of a range of analytical (filtering) parameters is critical to produce robust population genetic and demographic inferences (Mastretta‐Yanes et al., 2014; Paris, Stevens, & Catchen, 2017; Shafer et al., 2016). …”
Section: Genotyping Error and Improving Data Qualitymentioning
confidence: 99%
See 1 more Smart Citation